How developments in the science and technology of searching, recovering and identifying the missing/ disappeared are positively affecting the rights of victims around the world. (1st April 2017) - Sarkin, Jeremy
Abstract : This article examines the ways in which missing persons have been dealt with, mainly in the former Yugoslavia, to show how the huge advances made in the search for, recovery and identification of those who disappeared is positively impacting on the ability of families to find their loved ones. The article surveys the advances made in dealing with the missing on a range of fronts, including the technical and forensic capacities. It examines some of the other developments that have occurred around the world with regard to the search for, recovery and identification of people and makes recommendations on how to make improvements to ensure that the rights of families around the world, as well as a range of other human rights, including truth and justice, are enhanced.